Nova Sapho — Um novo olhar sob(re) a paisagem literária portuguesa - Silva, Clara Maria (CEM – Cultura, Espaço & Memória, 2021)
It’s our main goal to bring Nova Sapho of Visconde de Vila-Moura to the surface of the Portuguese literary landscape. Situated in the twentieth century, three years before the orphic modernist movement, this novel does not integrate the Portuguese’s literary canon. In Aníbal Fernandes’ words this is «the only and main example of the decadent movement in portuguese prose» (my translation) which explores feminine sexuality as marginal to the social and cultural context. Understanding decadent features within this work is our main goal and it will provide an introductory stance to the novel, being Anna M. Klobucka’s and Óscar Lopes’ studies the only investigation found about it.